Alat Pengukur Berat Badan dan Tinggi Badan Terkomputerisasi berbasis Wireless, Arduino, Sensor Load Cell, dan Ultrasonic - Muhamad Ichwan Sudibyo; Hurriyatul Fitriyah; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The measurenment of body weight and height are very common ineveryday life, but there are still many people who do the measurenment manually and separately. When measuring body weight, most people will use digital scales, and for measuring height using a meter. To overcome this problem, the researcher made a system that can measure body weight and height while storing data on body weight and height into the database so that can be seen at anytime. In this system the researcher will use load cell to measurenment of body weight and ultrasonic HC-SR04 censor to measurenment body height. In this study, the data transmission will use a wireless and can store data into the database. From the test result obtained, the data from the reading of weight censor load cell has average data 2.73 kilograms with difference in data of digital scales 0,01 - 0,30 kilograms, and for ultrasonic censor HC-SR04 has average data 0.7 centimeter with difference of meters 0.1 - 0.5 centimeters. Data transmission using the wireless sensor can transmit data to a maximum range of 15 meters. And the data you get can be saved into the database.